OPTIMIZATION OF ICE DISTRIBUTION USING VOGEL’S APPROXIMATION METHOD AT MOMOYO JAYAPURA STORE - Alyah Amri; Heru Sutejo, Olce Wehelmina Sibi, Albrianus Rheno Janggur, Albertina Vince Sineri, Naftali Kasitay (CV. Adiba Aisha Amira, 2026)
The goals of search to optimize the ice distribution system at Momoyo Entrop Jayapura Store using Vogel’s Approximation Method (VAM). A quantitative descriptive approach was employed, and data were collected through observation, interviews, and documentation. The transportation model considered three suppliers with a total supply of 300 units and three outlets with a total demand of 300 units. Penalty calculations showed the highest column index value of 2 for Outlet 2, which became the priority for allocation. The VAM results allocated 100 units from Supplier A to Outlet 3, 110 units from Supplier B to Outlet 2, 10 units from Supplier B to Outlet 1, and 80 units from Supplier C to Outlet 1. The total transportation cost obtained was IDR 1,790,000, lower than the initial cost of IDR 2,050,000, resulting in savings of IDR 260,000. Therefore, VAM effectively improves distribution efficiency.